Análisis multivariado de componentes terpénicos, en aceite esencial de hierba luisa (Cymbopogon citratus), mediante espectrofotometría UV - Visible Derivada - Gómez Araujo, Manuel Esteban (2017)
The aim of the present investigation is to evaluate the derivative ultraviolet-visible spectrophotometry as a viable scientific method for the determination of terpene components in essential oil of Lemon grass (Cymbopogon citratus). The UV-VIS Spectrophotometer V-730 from JASCO was used, with wavelengths between 400 and 190 nanometers to obtain data from dilutions composed of essential oil and n-heptane solvent in a scale of 1:500, alsocitral and α-pinene as standards. The Spectra Analysis software was used to obtain derivatives of each spectrum, from the first to the fourth order along with a debugging process. These data were processed in the PAST statistical software program version 2.17c through the use of the NMDS or Non-Metric Multidimensional Scaling techniques and by the Neighbor Joining cluster, which proved to be optimal in the ordering process for the second derivative spectral information, since the formation of clusters that presented as a function of the concentrations of citral and α-pinene allowed to interpret the possible chemical status of each essential oil, with a lower percentage of uncertainty, in regard to the other derivatives and to the original data.